Toilet Training Method Is Not Related to Dysfunctional Voiding. (January 2013) - Colaco, Marc; Johnson, Kelly; Schneider, Dona; Barone, Joseph
Background . Toilet training is an important marker of physical and psychosocial development, but the best strategy for implementing training is still unknown. The purpose of this study is to compare dysfunctional voiding outcomes for 2 common toilet training strategies: parent-oriented training and child-oriented training. Materials and methods . This study was completed using a case-control design, with participants between the ages of 4 and 12 years. All participants were asked to complete questionnaires related to demographics and toilet training method. Results were then analyzed between cases and controls. Results . In all, 215 patients with a mean age 7.76 years participated in this study. Cases and controls showed no significant difference for demographic measures and socioeconomic status. Furthermore, there was no significant difference in dysfunctional voiding between toilet training methods. Conclusion . Toilet training method does not seem to have any long-term effect on dysfunctional voiding. As such, clinicians should advise parents that both methods are acceptable.